Levonorgestrel long-acting slow-release implant and preparation method thereof

By combining the microcrystalline core and PLGA-PCL gradient coating of the levonorgestrel long-acting sustained-release implant, the problems of complex implantation, frequent dosing and drug concentration fluctuations of existing formulations are solved, achieving long-acting, minimally invasive and stable drug release, which is suitable for the field of contraceptives.

CN121129737APending Publication Date: 2025-12-16HAINAN VOCATIONAL COLLEGE OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511520056.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-23
Publication Date
2025-12-16

AI Technical Summary

Technical Problem

Existing levonorgestrel formulations have problems such as the need for surgical implantation and removal, frequent re-administration, excessively high initial drug concentration, and low precision in drug release rate control, making it difficult to achieve long-acting, minimally invasive, and stable drug release.

Method used

The long-acting sustained-release levonorgestrel implant contains a levonorgestrel microcrystalline core and a PLGA-PCL gradient degradation coating. It is prepared by micronization, antisolvent precipitation and fluidized bed coating technology to form a suspension that can be injected minimally invasively, achieving a long-acting drug release for 5 years.

Benefits of technology

It achieves long-term stable drug release for 5 years, reduces the frequency of administration, reduces the difficulty of operation and patient suffering, avoids drug concentration fluctuations, and the carrier is completely degraded without the need for secondary surgery, making it suitable for industrial mass production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of contraceptives, and discloses a levonorgestrel long-acting slow-release implant and a preparation method thereof, the levonorgestrel long-acting slow-release implant comprises the following components by mass: 10-20 parts of a levonorgestrel bulk drug, 25-35 parts of PCL, 40-50 parts of PLGA, 3-8 parts of a solid dispersant, and 3-8 parts of an injection solvent. According to the invention, a composite structure of a levonorgestrel microcrystalline core with a particle size of 5-20 [mu] m and a PLGA-PCL gradient degradation coating is adopted, and an injection solvent is mixed to form a minimally invasive injection suspension; the preparation method comprises the following steps: preparing microcrystals through anti-solvent precipitation, preparing a gradient coating through fluidized bed coating, and mixing to prepare a suspension, thereby obtaining the levonorgestrel long-acting slow-release implant. After being subjected to hypodermic injection through a 27G narrow needle, the nanomaterial is self-assembled into a 3mm columnar solid, can be completely degraded into CO2 and H2O, and has long-term effectiveness, minimally invasive property, degradability and drug release stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of contraceptive technology, and more specifically, to a long-acting sustained-release levonorgestrel implant and its preparation method. Background Technology

[0002] Levonorgestrel is a commonly used, highly effective progestin-based contraceptive in clinical practice. Its long-acting formulations mainly include three types: silicone rubber implants, biodegradable implants, and injectable microspheres. However, existing technologies have significant drawbacks: Silicone rubber implants (such as Nopstar): require surgical incision for implantation, and require surgical removal after a 3-year shelf life. Post-operative recovery time is 7-10 days, making the procedure complex, resulting in low patient compliance. Furthermore, the non-degradable silicone rubber carrier may cause local tissue irritation. Biodegradable implants (such as etogestrin implants): while not requiring surgical removal, have a release period of only 90 days, necessitating frequent re-administration and failing to meet long-term contraceptive needs. Injectable microsphere formulations: use a single polymer (such as PLGA) as a carrier, injected via a 23G needle. Post-operative recovery time is 48 hours, and an initial burst release rate >15% is common, leading to excessively high short-term drug concentrations. Moreover, the release period is often less than one year, resulting in poor long-term efficacy.

[0003] In addition, the existing formulations have low precision in drug release rate control, making it difficult to achieve the synergy of "5-year stable release" and "minimally invasive implantation". Therefore, it is of great practical significance to provide a levonorgestrel implant that can simultaneously have long-lasting effect, minimal invasiveness, biodegradability and drug release stability, especially suitable for people who need long-term contraception and pursue convenience and safety. Summary of the Invention

[0004] In view of this, the present invention proposes a long-acting sustained-release levonorgestrel implant and its preparation method, aiming to solve the problems of the current technology, which requires surgical implantation and removal, cannot meet the needs of long-term contraception, and uses a single polymer as a carrier, which can easily lead to excessively high drug concentration in the body in the short term and poor long-term efficacy.

[0005] This invention provides a long-acting sustained-release levonorgestrel implant, which comprises the following components in parts by weight: Levonorgestrel raw material 10-20 parts, PCL 25-35 parts, PLGA 40-50 parts, solid dispersant 3-8 parts, injection solvent 3-8 parts.

[0006] Furthermore, the solid dispersant is polyethylene glycol, and the injection solvent is benzyl benzoate.

[0007] Furthermore, the levonorgestrel raw material has a particle size of 5-10 μm after micronization.

[0008] Furthermore, the levonorgestrel long-acting sustained-release implant comprises a levonorgestrel microcrystalline core and a PLGA-PCL gradient degradation coating; The levonorgestrel microcrystalline core is made by mixing levonorgestrel raw material and solid dispersant at a mass ratio of 3:1; The gradient degradation coating comprises an inner PCL coating and an outer PLGA coating. The PCL has a molecular weight of 20,000, the PLGA has a lactic acid-glycolic acid molar ratio of 75:25 and a molecular weight of 30,000, and the thickness ratio of the PCL coating to the PLGA coating is 1:2.

[0009] The preparation method of the levonorgestrel long-acting sustained-release implant includes the following steps: (1) Preparation of levonorgestrel microcrystals: Levonorgestrel and solid dispersant were dissolved in dichloromethane to form an oil phase by antisolvent precipitation method. The oil phase was slowly added dropwise to PVA aqueous solution. After ultrasonic emulsification and rotary evaporation to remove solvent, the precipitate was collected by centrifugation and freeze-dried to obtain needle-shaped microcrystals. (2) Gradient coating: The needle-like microcrystals obtained in step (1) are coated. The coating includes a first coating and a second coating. The coating is carried out by fluidized bed coating. The first coating is to dissolve PCL in an acetone-chloroform mixture to form a PCL coating solution, which coats the needle-like microcrystals in step (1) to achieve initial weight gain and form an inner PCL coating. The second coating is to dissolve PLGA in an acetone-chloroform mixture to form a PLGA coating solution, which coats the PCL coating to achieve secondary weight gain and form an outer PLGA coating, thus obtaining coated microcrystals. (3) Preparation of injection suspension: The coating microcrystals obtained in step (2) are mixed with the injection solvent and dispersed at high speed to prepare the levonorgestrel long-acting sustained-release implant.

[0010] Furthermore, in step (1), the oil phase concentration is 10 mg / mL, the oil phase is slowly added dropwise to the PVA aqueous solution, the volume ratio of the oil phase to the PVA aqueous solution is 1:5, and the mass fraction of the PVA aqueous solution is 0.5%.

[0011] Furthermore, the ultrasonic emulsification parameters in step (1) are: frequency 40kHz, temperature 35℃, and time 3min; the rotary evaporation parameters are: temperature 30℃ and vacuum degree 0.021MPa.

[0012] Furthermore, the freeze drying in step (1) includes a pre-cooling stage, a sublimation drying stage, and a desorption drying stage. The parameters for the pre-cooling stage are: temperature -40~-35℃, cooling rate 5℃ / min, and time 2.5~3.5h. The parameters for the sublimation drying stage are: temperature -25~-20℃, vacuum degree 10Pa~30Pa, and holding time 24h~30h. The parameters for the desorption drying stage are: temperature 30~35℃, vacuum degree 1Pa~5Pa, and holding time 12h~18h.

[0013] Furthermore, in step (2), the volume ratio of acetone to chloroform in the acetone-chloroform mixture is 1:1, and the concentration of the PCL coating solution is 5%; the first coating parameters are: inlet air temperature 30℃, spray pressure 0.2MPa, and spray rate 5mL / min; the initial weight gain is 30%; the concentration of the PLGA coating solution is 8%; the second coating parameters are: inlet air temperature 35℃, spray pressure 0.2MPa, and spray rate 5mL / min; and the second weight gain is up to 45% of the total weight gain.

[0014] Furthermore, in step (3), the coating microcrystals and the injection solvent are mixed at a mass ratio of 9:1; the high-speed dispersion parameters are: time 2 min, rotation speed 10000-12000 rpm.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention achieves a 5-year long-lasting release through the synergistic effect of the PLGA-PCL gradient degradation coating and the microcrystalline core, far exceeding the 3-year lifespan of existing silicone rubber implants and the 90-day lifespan of biodegradable implants, thus reducing the frequency of drug administration.

[0016] The suspension encapsulated in the pre-filled syringe of this invention can be injected subcutaneously via a 27G narrow needle without surgical incision. The small puncture hole eliminates the need for anesthesia, promotes rapid postoperative recovery, reduces operational difficulty and patient discomfort, improves compliance, eliminates the risk of surgical infection and long-term tissue irritation, and avoids the trauma of secondary removal due to the completely degradable carrier. Furthermore, it can be operated by nurses in primary healthcare institutions, expanding clinical application scenarios and making it suitable for industrial mass production.

[0017] The dense structure of the microcrystalline core and the controlled release effect of the gradient coating in the levonorgestrel long-acting sustained-release implant of the present invention reduce the initial burst release rate, stabilize the daily release, and avoid the side effects caused by the initial drug concentration fluctuation.

[0018] The carrier of the levonorgestrel long-acting sustained-release implant described in this invention contains PCL, PLGA and excipients, all of which can be completely degraded into harmless CO2 and H2O, eliminating the need for secondary surgery to remove it and eliminating the risk of tissue irritation from long-term implantation. Detailed Implementation

[0019] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.

[0020] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included within this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0021] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0022] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0023] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0024] This invention provides a long-acting sustained-release levonorgestrel implant, which comprises the following components in parts by weight: Levonorgestrel raw material 10-20 parts, PCL 25-35 parts, PLGA 40-50 parts, solid dispersant 3-8 parts, injection solvent 3-8 parts.

[0025] In this invention, the levonorgestrel long-acting sustained-release implant is further preferably composed of the following components in parts by weight: 12-18 parts of levonorgestrel raw material, 25-35 parts of PCL, 40-50 parts of PLGA, 4-6 parts of solid dispersant, and 4-6 parts of injection solvent.

[0026] In this invention, the solid dispersant is polyethylene glycol, and the injection solvent is benzyl benzoate.

[0027] In this invention, the polyethylene glycol is preferably polyethylene glycol 6000.

[0028] In this invention, the levonorgestrel raw material has a particle size of 5~10μm after micronization.

[0029] The levonorgestrel long-acting sustained-release implant contains a composite structure of a levonorgestrel microcrystalline core and a PLGA-PCL gradient degradation coating. The composite structure, after being mixed with an injection solvent, forms a suspension that can be injected minimally invasively. The levonorgestrel microcrystalline core is formed by mixing levonorgestrel raw material and solid dispersant at a mass ratio of 3:1 and then micronizing the mixture, with a microcrystalline particle size of 5-20 μm. The gradient degradation coating comprises an inner PCL coating and an outer PLGA coating. The PCL has a molecular weight of 20,000, the PLGA has a lactic acid:glycolic acid molar ratio of 75:25 and a molecular weight of 30,000, and the thickness ratio of the PCL coating to the PLGA coating is 1:2.

[0030] In this invention, the core controlled-release carrier of the levonorgestrel long-acting sustained-release implant is PCL and PLGA. A gradient degradation coating structure with a PCL inner layer and a PLGA outer layer thickness ratio of 1:2 carries the levonorgestrel in the microcrystalline core. Polyethylene glycol serves as an auxiliary dispersion carrier, ensuring stable drug dispersion and preventing excessively high local concentrations caused by drug aggregation. This provides a foundation for uniform coating of the subsequent gradient layer, indirectly ensuring release stability. Benzyl benzoate serves as an injection molding carrier, enabling minimally invasive injection and subcutaneous molding. After injection, in the subcutaneous physiological environment, benzyl benzoate gradually... The drug is absorbed by the tissue and simultaneously guides the coating microcrystals to self-assemble into columnar solids with a diameter of 3 mm, enabling continuous local release of the drug and avoiding "concentration fluctuations" caused by drug diffusion. The carrier of this invention is not a single substance, but a carrier system composed of "gradient degradation controlled-release components, microcrystal dispersion components, and injection molding components". Each component carries levonorgestrel at different stages to achieve the goals of "long-acting sustained release, complete degradation, and minimally invasive injection". Through multi-functional synergy of controlled release, dispersion, and molding, and the fact that the carrier can be completely degraded into CO2 and H2O, eliminating the need for secondary surgery to remove it and eliminating the risk of tissue irritation from long-term implantation.

[0031] In this invention, polyethylene glycol (PEG) is selected as a solid dispersant in the long-acting sustained-release levonorgestrel implant. PEG can solve the "agglomeration problem" after levonorgestrel micronization, ensuring uniform microcrystal size. It can adsorb onto the surface of levonorgestrel micronized particles, forming a "hydrophilic protective film" that prevents direct contact between particles and reduces the driving force for agglomeration. The hydroxyl groups in the molecule can weakly ionize in aqueous solution, giving the particle surface a negative charge. Through the repulsion of like charges, the particles are further dispersed. The levonorgestrel crystallization process is regulated to form a stable "needle-shaped microcrystal" structure, which can act as a "crystal nucleus inhibitor," adsorbing onto specific growth surfaces of levonorgestrel crystals, slowing down the crystal growth rate along that direction, and preventing the formation of coarse crystals. This improves the "compatibility" of the microcrystals with subsequent processes, ensuring stable preparation and adapting to the entire "freeze-drying-fluidized bed coating-suspension preparation" process of this invention, solving key issues in process integration. It also improves the "bioavailability and safety" of levonorgestrel, meeting pharmaceutical requirements.

[0032] In this invention, the injectable solvent selected as benzyl benzoate in the levonorgestrel long-acting sustained-release implant is selected. Benzyl benzoate can match the hydrophobicity of the coating microcrystals, ensuring a stable and uniform suspension, achieving uniform dispersion, and preventing microcrystal aggregation or sedimentation. Furthermore, benzyl benzoate can regulate the in vivo absorption rate and promote the subcutaneous "columnar solid self-assembly." Benzyl benzoate is absorbed in subcutaneous tissue through "passive diffusion," with a half-life of approximately 48-72 hours. The solvent does not rapidly dissipate after injection, providing "36-48 hours of aggregation and self-assembly time" for the hydrophobic microcrystals—during the slow evaporation of the solvent, the microcrystals gradually aggregate through intermolecular hydrophobic interactions, ultimately forming "dense, regular columnar solids," preventing the microcrystals from diffusing with tissue fluid. The columnar solid structure can be considered as a "local drug reservoir," and levonorgestrel needs to diffuse through the gaps between microcrystals before being released through the degradation channels of the PCL / PLGA coating. The slow absorption process of benzyl benzoate is synchronized with the "initial degradation initiation of the coating," ensuring that the release rate is stable from the initial stage and avoiding initial burst release. As an excipient for injection, benzyl benzoate meets the requirements of "no reaction with drug / carrier, low local irritation, and no systemic toxicity." Its chemical inertness and biocompatibility ensure drug-tissue compatibility. Furthermore, its easy mixing with the coating microcrystals, lack of complex dispersion processes, and good storage stability can improve process compatibility and simplify the preparation and storage of suspensions.

[0033] In this invention, the levonorgestrel active pharmaceutical ingredient is micronized, with a particle size selected to be 5-10 μm. On one hand, micronization is a preliminary step in the antisolvent precipitation method to prepare "5-20 μm needle-like microcrystals." If the active pharmaceutical ingredient particle size is too large, it will lead to "excessively large initial particles" during antisolvent precipitation. Even after ultrasonic emulsification, coarse crystals >20 μm are easily formed, violating the core indicator of "microcrystal particle size 5-20 μm," thus affecting the uniformity of subsequent gradient coating. This invention ensures the controllability of particle size in subsequent microcrystal preparation. On the other hand, it can avoid release rate fluctuations during the sustained-release process. If the micronized active pharmaceutical ingredient has… Excessive use of large particles (>10μm) can lead to slower drug release rates for some large crystallites during gradient coating degradation, while smaller crystallites release drugs faster, ultimately deviating from the stable daily release range. Furthermore, large particles are prone to settling in the injection suspension, resulting in uneven dosage during injection and affecting contraceptive efficacy. Additionally, it ensures compatibility between freeze-drying and coating processes, preventing particle agglomeration during freeze-drying and maintaining a loose powder state. This provides uniform "base particles" for the subsequent inner PCL and outer PLGA layers, avoiding localized over-thickness or under-thickness of the coating due to particle agglomeration and ensuring precise achievement of the gradient coating thickness ratio.

[0034] The preparation method of levonorgestrel long-acting sustained-release implant includes the following steps: (1) Preparation of levonorgestrel microcrystals: Levonorgestrel and solid dispersant were dissolved in dichloromethane to form an oil phase by antisolvent precipitation method. The oil phase was slowly added dropwise to PVA aqueous solution. After ultrasonic emulsification and rotary evaporation to remove solvent, the precipitate was collected by centrifugation and freeze-dried to obtain needle-shaped microcrystals. (2) Gradient coating: The needle-like microcrystals obtained in step (1) are coated. The coating includes a first coating and a second coating. The coating is carried out by fluidized bed coating. The first coating is to dissolve PCL in an acetone-chloroform mixture to form a PCL coating solution, which coats the needle-like microcrystals in step (1) to achieve initial weight gain and form an inner PCL coating. The second coating is to dissolve PLGA in an acetone-chloroform mixture to form a PLGA coating solution, which coats the PCL coating to achieve secondary weight gain and form an outer PLGA coating, thus obtaining coated microcrystals. (3) Preparation of injection suspension: The coating microcrystals obtained in step (2) are mixed with the injection solvent and dispersed at high speed to prepare the levonorgestrel long-acting sustained-release implant.

[0035] In this invention, the suspension, after being injected subcutaneously, can self-assemble into a columnar solid with a diameter of 3 mm, and the columnar solid can be completely degraded into CO2 and H2O.

[0036] In this invention, the concentration of the oil phase in step (1) is 10 mg / mL, the oil phase is slowly added dropwise to the PVA aqueous solution, the volume ratio of the oil phase to the PVA aqueous solution is 1:5, and the mass fraction of the PVA aqueous solution is 0.5%.

[0037] In this invention, the ultrasonic emulsification parameters are: frequency 40kHz, temperature 35℃, and time 3min; the rotary evaporation parameters are: temperature 30℃ and vacuum degree 0.021MPa.

[0038] This invention employs a temperature of 30°C and a vacuum of 0.021 MPa during rotary evaporation. The 0.021 MPa vacuum represents a system pressure below atmospheric pressure, a precise choice considering both solvent characteristics and drug stability. Firstly, it lowers the solvent boiling point, achieving "low-temperature removal of dichloromethane" while protecting the activity of levonorgestrel and preventing thermal degradation that could lead to a decrease in drug content. Secondly, it avoids violent solvent boiling, protecting the microcrystalline "needle-like structure" and particle size uniformity, and providing a uniform substrate for subsequent coating thickness. Furthermore, it can... Improving solvent removal efficiency in aqueous solutions reduces residual solvent content and also complements subsequent centrifugation processes, ensuring easy collection of precipitates. However, if the vacuum is too high, the boiling point of dichloromethane will be too low, dropping below 25°C, resulting in an excessively rapid evaporation rate. This can cause a sudden drop in the temperature of the rotating flask's inner wall, leading to freezing of the aqueous PVA solution and hindering solvent evaporation. It may also cause microcrystals to agglomerate due to low temperatures. Conversely, if the vacuum is too low, the boiling point of dichloromethane will rise above 35°C, requiring an increase in the rotation temperature to 35-40°C. This increases the risk of drug degradation and reduces solvent removal efficiency, making it easier for residual amounts to exceed standards.

[0039] In this invention, the freeze-drying process includes a pre-cooling stage, a sublimation drying stage, and a desorption drying stage. The pre-cooling stage parameters are preferably: temperature -40~-35℃, cooling rate 5℃ / min, and time 2.5~3.5h; more preferably: temperature -38~-35℃, cooling rate 5℃ / min, and time 3~3.5h. The sublimation drying stage parameters are preferably: temperature -25~-20℃, vacuum degree 10Pa~30Pa, and holding time 24h~30h; more preferably: temperature -23~-20℃, vacuum degree 20Pa~30Pa, and holding time 25h~30h. The desorption drying stage parameters are preferably: temperature 30~35℃, vacuum degree 1Pa~5Pa, and holding time 12h~18h; more preferably: temperature 32~35℃, vacuum degree 2Pa~5Pa, and holding time 15h~18h.

[0040] In this invention, the volume ratio of acetone to chloroform in the acetone-chloroform mixture in step (2) is 1:1, and the concentration of the PCL coating solution is 5%; the first coating parameters are: inlet air temperature 30℃, spray pressure 0.2MPa, and spray rate 5mL / min; the initial weight gain is 30%; the concentration of the PLGA coating solution is 8%; the second coating parameters are: inlet air temperature 35℃, spray pressure 0.2MPa, and spray rate 5mL / min; and the second weight gain is up to 45% of the total weight gain.

[0041] In this invention, the coating microcrystals and the injection solvent in step (3) are mixed at a mass ratio of 9:1; the high-speed dispersion parameters are: time 2 min, rotation speed 10000-12000 rpm.

[0042] In this invention, unless otherwise specified, all raw materials required for preparation are commercially available products well known to those skilled in the art.

[0043] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0044] Example 1 1. Microcrystal preparation: Weigh 15g of levonorgestrel and 5g of PEG6000, dissolve them in 2L of dichloromethane to form an oil phase with a concentration of 10mg / mL; add the oil phase dropwise to 10L of 0.5% PVA aqueous solution, and simultaneously sonicate at 40kHz and 35℃ for 3min to form a homogeneous emulsion; place the emulsion in a rotary evaporator and remove the solvent dichloromethane by rotary evaporation at 30℃ and 0.021MPa, centrifuge at 3000rpm for 10min to obtain a precipitate; place the precipitate in a freeze dryer and freeze-dry it according to the parameters of "pre-freezing -38℃, 3h → sublimation -22℃, 20Pa, 27h → desorption 32℃, 3Pa, holding for 15h" to obtain needle-like microcrystals; 2. Gradient Coating: Weigh 30g of PCL and dissolve it in 600mL of acetone-chloroform (1:1 volume ratio) to obtain a 5% PCL coating solution. Place the needle-shaped microcrystals obtained in step 1 in a fluidized bed, set the spray pressure to 0.2MPa, the inlet air temperature to 30℃, and the spray rate to 5mL / min. Coat the microcrystals with the PCL coating solution until the microcrystals gain 30% of their weight, forming an inner PCL coating, to obtain the first-coated microcrystals. Then, dissolve 45g of PLGA in 562.5mL of acetone-chloroform (1:1 volume ratio) to obtain an 8% PLGA solution. Adjust the inlet air temperature to 35℃, keep the spray pressure and rate constant, and coat until the total weight gain is 45%, forming an outer PLGA coating, to obtain the second-coated coated microcrystals. 3. Preparation of suspension: Take 27g of the coated microcrystals obtained in step 2, add 3g of benzyl benzoate, place them in a high-speed disperser, disperse at 11000rpm for 2min to prepare a homogeneous suspension, and dispense into 1mL pre-filled syringes (each syringe contains 75mg of levonorgestrel).

[0045] Example 2 1. Microcrystal preparation: Weigh 12g of levonorgestrel and 4g of PEG6000, dissolve them in 1.6L of dichloromethane to form an oil phase with a concentration of 10mg / mL; add the oil phase dropwise to 8L of 0.5% PVA aqueous solution, and simultaneously sonicate at 40kHz and 35℃ for 3min to form a homogeneous emulsion; place the emulsion in a rotary evaporator, and remove the solvent dichloromethane by rotary evaporation at 30℃ and 0.021MPa, centrifuge at 3000rpm for 10min to obtain a precipitate; freeze-dry the precipitate by "pre-freezing at -36℃ for 3h → sublimation at 23℃, 20Pa for 25h → desorption at 32℃, 2Pa, and holding for 15h" to obtain needle-like microcrystals; 2. Gradient Coating: Dissolve 28g of PCL in 560mL of acetone-chloroform (volume ratio 1:1) to obtain a 5% PCL coating solution. Place the microcrystals obtained in step 1 in a fluidized bed, set the spray pressure to 0.2MPa, the inlet air temperature to 30℃, and the spray rate to 5mL / min. Coat the microcrystals with the PCL coating solution until the microcrystals gain 30% of their weight, forming an inner PCL coating, to obtain the first-coated microcrystals. Then, dissolve 43g of PLGA in 537.5mL of acetone-chloroform (volume ratio 1:1) to obtain an 8% PLGA solution. Adjust the inlet air temperature to 35℃, keep the spray pressure and rate constant, and coat until the total weight gain is 45%. Coat until the total weight gain is 45% at the inlet air temperature of 35℃ to form an outer PLGA coating, to obtain the second-coated coated microcrystals. 3. Preparation of suspension: Take 45g of the coated microcrystals obtained in step 2, add 5g of benzyl benzoate, place them in a high-speed disperser, disperse at 10000rpm for 2min to prepare a homogeneous suspension, and dispense into 1mL pre-filled syringes (each syringe contains 75mg of levonorgestrel).

[0046] Example 3 1. Microcrystal preparation: 18g of levonorgestrel and 6g of PEG6000 were weighed and dissolved in 2.4L of dichloromethane to form an oil phase with a concentration of 10mg / mL; the oil phase was added dropwise to 12L of 0.5% PVA aqueous solution, and simultaneously ultrasonically emulsified at 40kHz and 35℃ for 3min to form a homogeneous emulsion; the emulsion was placed in a rotary evaporator and the solvent dichloromethane was removed by rotary evaporation at 30℃ and 0.021MPa, and centrifuged at 3000rpm for 10min to obtain a precipitate; the precipitate was freeze-dried in a freeze dryer according to the following procedure: pre-freezing at -35℃ for 3.5h → sublimation at -20℃ for 30Pa for 30h → desorption at 35℃ for 5Pa for 18h to obtain needle-like microcrystals; 2. Gradient Coating: Dissolve 32g of PCL in 640mL of acetone-chloroform (volume ratio 1:1) to obtain a 5% PCL coating solution. Place the microcrystals obtained in step 1 in a fluidized bed, set the spray pressure to 0.2MPa, the inlet air temperature to 30℃, and the spray rate to 5mL / min. Coat the microcrystals with the PCL coating solution until the microcrystals gain 30% of their weight, forming an inner PCL coating, to obtain the first-coated microcrystals. Then, dissolve 47g of PLGA in 587.5mL of acetone-chloroform (volume ratio 1:1) to obtain an 8% PLGA solution. Adjust the inlet air temperature to 35℃, keep the spray pressure and rate constant, and coat until the total weight gain is 45%. Coat until the total weight gain is 45% at the inlet air temperature of 35℃ to form an outer PLGA coating, to obtain the second-coated coated microcrystals. 3. Preparation of suspension: Take 63g of the coated microcrystals obtained in step 2, add 7g of benzyl benzoate, place them in a high-speed disperser, disperse at 12000rpm for 2min to prepare a homogeneous suspension, and dispense into 1mL pre-filled syringes (each syringe contains 75mg of levonorgestrel).

[0047] Performance testing The performance test results of the levonorgestrel long-acting sustained-release implants described in Examples 1-3 are as follows: 1. Release rate test: The levonorgestrel long-acting sustained-release implants described in Examples 1-3 were all injected into a gel matrix of simulated subcutaneous tissue using a 27G narrow needle. The implants were placed in pH 7.4 phosphate buffer and the release rate was measured using a 50 rpm paddle method. In Example 1, the release rate was 4.2% in 1 day, 29.8% in 1 year, 61.5% in 3 years, and 96.3% in 5 years, with the daily release rate remaining stable at 22-28 μg. In Example 2, the release rate was 3.8% in 1 day, 29.7% in 1 year, 61.2% in 3 years, and 96.5% in 5 years, with the daily release rate remaining stable at 22.3-28.5 μg. In Example 3, the release rate was 3.8% in 1 day, 29.5% in 1 year, 61.2% in 3 years, and 96.8% in 5 years, with the daily release rate remaining stable at 19.9-30.3 μg.

[0048] 2. Degradability test: After the suspensions in Examples 1-3 were injected via a 27G narrow needle, the test results showed that after 3 months of injection, the outer PLGA coating microcrystal began to degrade; after 24 months, the inner PCL layer was completely degraded; and after 36 months, the microcrystal core was completely degraded into CO2 and H2O with no residue. Its self-assembled columnar solid disappeared, and there were no solid particles or clumps.

[0049] 3. Minimally invasive test: In Examples 1-3, the suspension was administered subcutaneously to the back of 6-month-old male New Zealand rabbits using a 27G insulin needle. The injection process took less than 10 seconds, with no bleeding or swelling. The rabbits moved normally after the injection, proving that the minimally invasive test was achieved.

[0050] The "complete degradation of the carrier within 36 months" in the degradation test of this application is a necessary condition, not a limiting condition, for "long-acting drug release over 5 years". The release of levonorgestrel depends on "pore diffusion formed by carrier degradation" and "slow dissolution of the core". Even if the carrier is completely degraded within 36 months, the drug that has diffused into the subcutaneous microenvironment through the carrier pores in the early stage can still be continuously released through the concentration gradient. If the carrier degradation is too slow, such as taking 5 years to completely degrade, it will lead to the obstruction of drug release in the later stage and the excessive residual amount. The current 36-month degradation design achieves "early degradation of the carrier but continuous release of the drug" through "gradient controlled release", which satisfies the safety requirement of "no carrier residue" and achieves the efficacy goal of "long-acting drug release over 5 years". The two are unified through precise material ratio and process parameters.

[0051] In summary, the levonorgestrel long-acting sustained-release implant prepared by this invention can reduce the initial burst release rate and stabilize the daily release through the dense structure of its microcrystalline core and the controlled release effect of the PLGA-PCL gradient coating, avoiding the side effects caused by initial drug concentration fluctuations. Furthermore, the synergistic effect of the PLGA-PCL gradient degradation coating and the microcrystalline core can achieve a long-acting release for 5 years. Its carrier and excipients can be completely degraded into harmless CO2 and H2O, eliminating the need for secondary surgery to remove it and eliminating the risk of tissue irritation from long-term implantation.

[0052] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the present invention. The scope of protection of the present invention is determined by the appended claims.

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A long-acting sustained-release levonorgestrel implant, characterized in that, The levonorgestrel long-acting sustained-release implant comprises the following components in parts by weight: Levonorgestrel raw material 10-20 parts, PCL 25-35 parts, PLGA 40-50 parts, solid dispersant 3-8 parts, injection solvent 3-8 parts.

2. The levonorgestrel long-acting sustained-release implant according to claim 1, characterized in that, The solid dispersant is polyethylene glycol, and the injection solvent is benzyl benzoate.

3. The levonorgestrel long-acting sustained-release implant according to claim 1, characterized in that, The particle size of the levonorgestrel raw material is 5~10μm.

4. The levonorgestrel long-acting sustained-release implant according to claim 1, characterized in that, The levonorgestrel long-acting sustained-release implant contains a levonorgestrel microcrystalline core and a PLGA-PCL gradient degradation coating. The levonorgestrel microcrystalline core is made by mixing levonorgestrel raw material and solid dispersant at a mass ratio of 3:1; The gradient degradation coating comprises an inner PCL coating and an outer PLGA coating. The PCL has a molecular weight of 20,000, and the PLGA has a molar ratio of lactic acid to glycolic acid of 75:25 and a molecular weight of 30,000. The thickness ratio of the PCL coating to the PLGA coating is 1:

2.

5. A method for preparing a long-acting sustained-release levonorgestrel implant as described in any one of claims 1-4, characterized in that, Includes the following steps: (1) Preparation of levonorgestrel microcrystals: The antisolvent precipitation method was used to dissolve levonorgestrel raw material and solid dispersant in dichloromethane to form an oil phase. The oil phase was slowly dripped into PVA aqueous solution. After ultrasonic emulsification and rotary evaporation to remove the solvent, the precipitate was collected by centrifugation and freeze-dried to obtain needle-shaped microcrystals. (2) Gradient coating: The needle-like microcrystals obtained in step (1) are coated. The coating includes a first coating and a second coating. The coating is carried out by fluidized bed coating. The first coating is to dissolve PCL in an acetone-chloroform mixture to form a PCL coating solution, which coats the needle-like microcrystals in step (1) to achieve initial weight gain and form an inner PCL coating. The second coating is to dissolve PLGA in an acetone-chloroform mixture to form a PLGA coating solution, which coats the PCL coating to achieve secondary weight gain and form an outer PLGA coating, thus obtaining coated microcrystals. (3) Preparation of injection suspension: The coating microcrystals obtained in step (2) are mixed with the injection solvent and dispersed at high speed to prepare the levonorgestrel long-acting sustained-release implant.

6. The method for preparing the levonorgestrel long-acting sustained-release implant according to claim 5, characterized in that, In step (1), the oil phase concentration is 10 mg / mL. The oil phase is slowly added dropwise to the PVA aqueous solution. The volume ratio of the oil phase to the PVA aqueous solution is 1:

5. The mass fraction of the PVA aqueous solution is 0.5%.

7. The method for preparing the levonorgestrel long-acting sustained-release implant according to claim 5, characterized in that, The ultrasonic emulsification parameters are: frequency 40kHz, temperature 35℃, and time 3min; the rotary evaporation parameters are: temperature 30℃ and vacuum degree 0.021MPa.

8. The method for preparing the levonorgestrel long-acting sustained-release implant according to claim 5, characterized in that, The freeze drying in step (1) includes a pre-cooling stage, a sublimation drying stage, and a desorption drying stage. The parameters for the pre-cooling stage are: temperature -40~-35℃, cooling rate 5℃ / min, and time 2.5~3.5h. The parameters for the sublimation drying stage are: temperature -25~-20℃, vacuum degree 10Pa~30Pa, and holding time 24h~30h. The parameters for the desorption drying stage are: temperature 30~35℃, vacuum degree 1Pa~5Pa, and holding time 12h~18h.

9. The method for preparing the levonorgestrel long-acting sustained-release implant according to claim 5, characterized in that, In step (2), the volume ratio of acetone to chloroform in the acetone-chloroform mixture is 1:1, and the concentration of the PCL coating solution is 5%. The first coating parameters are: inlet air temperature 30℃, spray pressure 0.2MPa, and spray rate 5mL / min. The initial weight gain is 30%. The concentration of the PLGA coating solution is 8%. The second coating parameters are: inlet air temperature 35℃, spray pressure 0.2MPa, and spray rate 5mL / min. The second weight gain is up to 45% of the total weight gain.

10. The method for preparing the levonorgestrel long-acting sustained-release implant according to claim 6, characterized in that, In step (3), the coating microcrystals and the injection solvent are mixed at a mass ratio of 9:1; the high-speed dispersion parameters are: time 2 min, rotation speed 10000-12000 rpm.